Governança relacional na terceirização de tecnologia da informação: o papel da Teoria da Autodeterminação e o efeito mediador do controle percebido pelos gestores públicos - FRIAES, Ligiane Cristina Braga de Oliveira (Universidade Federal do Pará, 2023)
Researchers in the field recognize the importance of the relationship between contractor and contractee in the process of Information Technology (IT) outsourcing. However, little is known about the impact of the manager's profile in this process. Thus, the objective of this research was to analyze the impact of the perception of competence, autonomy and relationship of public managers on Relational Governance (RG), as well as, to identify the effect of perceived control in this relationship. Design/methodology/approach: This study uses a quantitative approach to investigate the impact of the behavioral characteristics of IT managers from the Self-Determination Theory (SDT). The data were collected in Brazilian public institutions active in the areas of education, finance, statistics, and technology, and the hypotheses were identified and evaluated using the technique of Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The results identified that managers' selfdetermination is related to the perception of control, which consequently this impacts the RG by providing feelings of competence and autonomy capable of building a beneficial relationship with the IT provider. Practical implications: This study, promotes the understanding that upper management needs to support the autonomy of managers to increase their levels of intrinsic motivation when managing supplier deliveries. Originality/value: The application of Self-Determination Theory, to the IT Outsourcing context, provides new insights into the mediation of perceived control by explaining the relationship between managers' expectations and motivations as an important driver for RG.